Effect of footwear features on the gait muscle activity of middle-aged and older adults - Yang, Jinlong (2014)
The world population is aging at a faster pace. Muscle mass and strength deteriorates with the increase in age. Regular exercise has been reported to improve the musculoskeletal health for the older adults. Previous studies reported that walking was the most preferred exercise for the older adults. Different footwear has been reported to affect the muscles and the gait cycle muscle activity pattern. The purpose of this project is to compare the gait muscle activity effect of three commercially available exercise shoes (FitFlop, MBTTM, and Adidas Adipure Trainer 1.1) with respect to a normal control shoe of minimal features. Three different age groups of subjects were tested, young (20 – 30 years old), middle-aged (40 – 60 years old) and older adults (60+ years old). Ten lower muscles will be studied in this experiment and how the different footwear affects them during the 5 different phases of a gait cycle, primarily for the middle-aged and older adults. Muscles activities were recorded wireless with an EMG system and analysed by MEGAWIN software. Raw EMG data were RMS smoothed and analysed. Student t-tests were performed to validate the statistical differences (P < 0.05) between the shoes across all age groups, for IEMG values under the gait cycle and the normalised amplitude. Significant differences in muscle activity for the older adults were observed for 3 muscles (GM, VM, and TA) for MBT. FitFlop did not exhibit any significant muscle activities except for 1 muscle (SEM) for the old subjects. Adidas Adipure Trainer 1.1 exhibited the most statistical differences (P < 0.05) for 7 muscles (SOL, GM, GL, VM, VL, BF and TA) in older adults.